Similarities between two-part sentences in Chinese and Kazakh languages - Aбдурaкын Н, Н; Мaулет, Б. (Journal of Oriental Studies, 2018)
In this article we comprehensively conducted similarities between two-part sentences in Chinese and Kazakh language. According to the thinking of Chinese people the order of thought is determined like: doer of the action + action + receiver of the action. In accordance with grammar: the subject + the predicate + the object. According to the thinking of Kazakh people the order of thought is determined like: doer of the action+ receiver of the action + action. In accordance with grammar: the subject + the object + the predicate. Also, other similarities were researched in this article.